Description of a new kinorhynch species, Paracentrophyes sanchezae n. sp. (Kinorhyncha: Allomalorhagida) from the Gulf of Mexico, with differential notes on one additional, yet undescribed species of the genus - Sørensen, Martin V.; Landers, Stephen C. (Zootaxa, 2017)
A new kinorhynch species, Paracentrophyes sanchezae n. sp., is described from the Gulf of Mexico. The new species is distinguished from its congeners by its relatively low number of perispinal setae. In addition to the new species, the existence of one undescribed species of Paracentrophyes in the Gulf of Mexico is also reported. This undescribed species has very short lateral terminal spines, and the number of perispinal setae is lower than in any other known species of Paracentrophyes. Diagnostic notes are provided for this unnamed species, but the available material is too limited to provide a formal description.